The Role of Soft Total Quality Management Towards Operational Performance at PT Sier - Wibowo, Anetta Tizianka; FCW Sutrisno, Timotius; Hendrika Kenang, Irantha (School of Business, Bogor Agricultural University (SB-IPB), 2023)
Every firm needs to adapt in the global business environment so that can still sustain in the midst of intense competition. One of the tools that can be used is using soft Total Quality Management (TQM). The purpose of this research is to analyse the role of soft TQM implementation towards operational performance at PT Surabaya Industrial Estate Rungkut (SIER). The variables that are used are soft TQM elements, that is, top management commitment, continuous improvement, training and education, customer focus, process management, workforce management, and supplier relationship. This research uses quantitative method through questionnaire. The population in this research are PT SIER employees with the level of position as an officer from logistics, SIER strategic business unit, and supporting service division. The sampling technique that is used is proportional stratified random sampling that then results the total sample of 72 people. Data is analysed using SEM-PLS method with SmartPLS 3 software. Based on the results of the research can be concluded that from all elements of soft TQM only top management commitment, customer focus, and supplier relationship that are found have positive and significant effect towards operational performance at PT SIER. Keywords: total quality management, soft total quality management, quality management, operational performance, industrial estate